Three-dimensional temporal migration according to initial data of areal seismic exploration - V. N. Pilipenko; A. O. Verpakhovskaya; V. B. Budkevich (Геофизический журнал, 2016)
Migration methods are traditionally subdivided into two groups depending on carrying out the procedure of summing up the route by the method of common deep point (CDP): before and after summing up (pre- and post-stack migration in English variant). Despite the fact that while processing seismic data we use post-stack migration more often, pre-stack migration allows producing deep image of geological medium in more details that naturally increases the quality of interpretation of seismic exploration data. Therefore in the case when we need to study all the features of deep structure of geological environment, pre-stack migration will give us more informative result, especially while processing the data of areal seismic exploration in the areas with complicated tectonics. A variant of three-dimensional temporal finite-difference pre-stack migration has been proposed based on reverse extension of the wave field in temporal scale of depth, realized by solving of wave equation by obvious residual scheme. This approach guarantees a correct and steady solving of the problem of producing three-dimensional image of the environment demonstrated by practical example of processing the data, observed in Krasnolymansk area (Donbass region).